2021
DOI: 10.1002/hpm.3262
|View full text |Cite
|
Sign up to set email alerts
|

Financial sustainability strategies of public primary health care centres in the Republic of Srpska, Bosnia and Herzegovina

Abstract: Background: The literature on the functioning of public health facilities in health systems with significant arrears is limited. The growing liabilities of health facilities and the accumulating arrears have been a challenge in the Republic of Srpska. Most public primary healthcare (PHC) centres generated a gross loss in 2018. Method: Guided by the 'positive deviance' approach, we used an exploratory case study design to identify strategies used by managers to achieve financial sustainability in eight top-perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The findings reveal that successfully implementing the FM program requires revising and improving resource identification, resource pooling, service delivery methods, payment system models, implementation processes, and management structures within PHC financing. Health financing policies play a crucial role in achieving UHC, and each country's progress toward this goal is influenced by its healthcare financing methods 28,29 . The financial arrangements within health service delivery systems greatly impact the delivery of PHC, encompassing the funding received, fund transfer methods, and incentives provided for payment to healthcare providers 6 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings reveal that successfully implementing the FM program requires revising and improving resource identification, resource pooling, service delivery methods, payment system models, implementation processes, and management structures within PHC financing. Health financing policies play a crucial role in achieving UHC, and each country's progress toward this goal is influenced by its healthcare financing methods 28,29 . The financial arrangements within health service delivery systems greatly impact the delivery of PHC, encompassing the funding received, fund transfer methods, and incentives provided for payment to healthcare providers 6 …”
Section: Discussionmentioning
confidence: 99%
“…Health financing policies play a crucial role in achieving UHC, and each country's progress toward this goal is influenced by its healthcare financing methods. 28,29 The financial arrangements within health service delivery systems greatly impact the delivery of PHC, encompassing the funding received, fund transfer methods, and incentives provided for payment to healthcare providers. 6 Moghaddam et al identified challenges in the FM program, including insufficient overall financial resources, unstable funding, and a lack of coherence in the management of the financing system system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation